Impact of deceased-donor characteristics on early graft function: outcome of kidney donor pairs accepted for transplantation - Mahler, Christoph F.; Friedl, Felix; Nusshag, Christian; Speer, Claudius; Benning, Louise; Göth, Daniel; Schaier, Matthias; Sommerer, Claudia; Mieth, Markus; Mehrabi, Arianeb; Renders, Lutz; Heemann, Uwe; et al. (Frontiers in Immunology, 2024)
The impact of deceased donor characteristics on kidney transplant outcomes is controversial.Correspondingly, the predictive performance of deceased donor scores remains moderate and many transplant centres lack validated criteria for graft acceptance decisions. To better dissect donor related risk from recipient and periprocedural variables, we analysed outcomes of kidney donor pairs transplanted in different individuals.This study explored (a)symmetry of early outcomes of 328 cadaveric kidney transplant recipients from 164 donor pairs transplanted at three Eurotransplant centres. The primary discriminatory factor was (a)symmetry of partner graft function, defined as early graft los (EGL) or impaired graft function (eGFR <30ml/min) three months after transplantation. We reasoned a relevant impact of donor factors would result in a high concordance rate of limited graft function or failure.The observed number of symmetric graft failure after transplantation was less than statistically expected (3 months: 1 vs 2, p=0.89 and 12 months: 3 vs 5, p=0.26) However, we found a trend towards an impaired five-year graft survival of grafts with good function three months after transplantation but a failed or impaired partner graft compared to symmetrically wellfunctioning grafts (p=0.09). Subsequently, we explored the impact of individual donor-and recipient variables on early transplant outcomes. Generalized Estimating Equations after feature selection with LassoGEE bootstrap selected donor age, donor BMI and donor eGFR as relevant risk factors.Our findings indicate, that donor factors impact early outcomes in kidney transplantation, but may have a limited role in long term graft survival, once a graft has been accepted for transplantation. Utilizing donor-based clinical scores has the potential to aid clinicians in acceptance decisions, giving them an estimate of individual post-transplant outcomes.However, the ultimate decision for acceptance should rest with clinicians, who must consider the complex interplay of donor factors, as well as recipient and periprocedural characteristics.